Development Of Dus Standard For Taro [Colocasia Esculenta Var. Antiquirom (L.) Schott.] Using Digital Morphometrics (Applied Biological Research, 2015)
The leaves, tubers and other morpho-culinary characters of nine taro  [Colocasia esculenta var. antiquirom (L) Schott.] cultivars were considered  for development of distinct, uniform and stable (DUS) standards using  digital morphometrics and computational methods besides taking help  from prototypes of hand-held digital field guides and various robotic  systems to bring them under IPR-related regimes. Out of 48 morpho culinary characters studied maximum were polymorphic in nature. Some  cultivars possessed unique stable characters helpful for their identification.  The study revealed that DUS descriptors using digital morphometrics can  be used effectively for identification and grouping of taro germplasm.
Keywords: Digital morphometrics; DUS; taro